The Effectiveness of Virtual Labs in Enhancing the Level of Perception of Physics Subject among the Secondary School Students and using them instead of the traditional ones at Al-Afiya Secondary School in municipality of Brack – Libya - Ibrahim Abdulrahman (Wadi Alshatti University Journal of Pure and Applied Sciences, 2025)
This study deals with identifying the impact of virtual laboratories on the level of educational attainment among Secondary school students in understanding physics in theory and linking it to the practical aspect, which is the most important to enhance the students' abilities and understand the subject easily, by conducting experiments inside the virtual laboratory instead of the traditional laboratory, which is short of equipment needed to conduct experiments by the students. An experiment that simulates the practical reality of the experience of the principle of torque balance was recorded from the physics book for the first year of secondary school in the form of a video and presented to students in a secondary school. To test the research hypotheses, the research tool was applied to a sample of 40 students distributed to two control and experimental groups. The results of the achievement and observation scale showed the effect of using the virtual laboratory in which it increases the students' mental ability and works on developing their understanding and remembering skills. The use of software also contributed to create an attractive and interesting learning environment suitable for the different abilities of the students. The virtual laboratory contributed to clarifying abstract concepts, especially those related to movement, which is otherwise difficult to explain on the traditional blackboard. The study recommends taking advantage of the virtual laboratory technology, especially in the absence of a school laboratory or lack of tools and equipment, and supports teaching by using educational presentations and e-learning.